Religious Motivation and the Origins of Buddhism - Brekke, Torkel (Routledge Critical Studies in Buddhism, 2002)
Why did people in North India from the 5th century BC choose to leave the world and join the sect of the Buddha? This is the first book to apply the insights of social psychology in order to understand the religious motivation of the people who constituted the early Buddhist community. It also addresses the more general and theoretically controversial question of how world religions come into being, by focusing on the conversion process of the individual believer.